2021
DOI: 10.1038/s41467-020-20241-w
|View full text |Cite
|
Sign up to set email alerts
|

Perineuronal nets stabilize the grid cell network

Abstract: Grid cells are part of a widespread network which supports navigation and spatial memory. Stable grid patterns appear late in development, in concert with extracellular matrix aggregates termed perineuronal nets (PNNs) that condense around inhibitory neurons. It has been suggested that PNNs stabilize synaptic connections and long-term memories, but their role in the grid cell network remains elusive. We show that removal of PNNs leads to lower inhibitory spiking activity, and reduces grid cells’ ability to cre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 1,525 publications
(59 citation statements)
references
References 74 publications
6
45
1
Order By: Relevance
“…However, if rats are re-exposed one time to a session in which they have to learn a new rule that is less predictable (average of five lever presses = one cocaine infusion), PNN removal now severely decreases cue recall the next day and for several days afterward. This suggests that exposure to a similar but new rule in the absence of PNNs degrades the original memory, akin to the grid cell findings (Christensen et al, 2021). These findings are consistent with the idea that, if PNN removal reduces the ability of PV interneurons to fire at higher frequencies that mediate sparse coding, it follows that suppression of PV interneurons increases the cell overlap for two stimuli that originally had separate representation in the brain (Figure 3; Agetsuma et al, 2018).…”
Section: Impact Of Pnn Removal On Circuits and Implications For Memory And Behaviorsupporting
confidence: 72%
See 1 more Smart Citation
“…However, if rats are re-exposed one time to a session in which they have to learn a new rule that is less predictable (average of five lever presses = one cocaine infusion), PNN removal now severely decreases cue recall the next day and for several days afterward. This suggests that exposure to a similar but new rule in the absence of PNNs degrades the original memory, akin to the grid cell findings (Christensen et al, 2021). These findings are consistent with the idea that, if PNN removal reduces the ability of PV interneurons to fire at higher frequencies that mediate sparse coding, it follows that suppression of PV interneurons increases the cell overlap for two stimuli that originally had separate representation in the brain (Figure 3; Agetsuma et al, 2018).…”
Section: Impact Of Pnn Removal On Circuits and Implications For Memory And Behaviorsupporting
confidence: 72%
“…This juvenile-like network state induced by Ch-ABC led to immediate increases in gamma activity after monocular deprivation (see “Impact of PNN Removal on Brain Oscillations” section). In a second study by the same group, and only the second study to examine in vivo putative inhibitory neurons following PNN removal, Christensen et al ( 2021 ) found that Ch-ABC treatment in the medial entorhinal cortex produced a similar decrease in the mean firing rate of putative inhibitory neurons. This matched their findings in the visual cortex and suggests that PV interneurons have increased spiking variability and decreased spiking rates when measured in vivo .…”
Section: Impact Of Pnn Depletion On Pv and Principal Neurons Plasticity And Brain Oscillationsmentioning
confidence: 99%
“…Work over the past several decades has elucidated the critical role of these structures in a broad range of processes, including synaptic plasticity and regulation of electrophysiological properties (Kalb and Hockfield, 1988;Sugiyama et al, 2008;Gogolla et al, 2009). PNNs are involved in regulating several functional neuronal properties, including somatic inhibition, glutamate receptor trafficking, and synaptic stabilization (Pizzorusso et al, 2002;Frischknecht et al, 2009;Frischknecht and Gundelfinger, 2012;Carceller et al, 2020;Christensen et al, 2021). For example, removal of PNNs decreases densities of inhibitory and excitatory synapses on the soma of PVB neurons (Carceller et al, 2020), reduces gamma activity (Christensen et al, 2021), and de-stabilizes the grid cell network (Christensen et al, 2021).…”
Section: Extracellular Matrix: Evidence For Involvement In Memory Consolidationmentioning
confidence: 99%
“…PNNs are involved in regulating several functional neuronal properties, including somatic inhibition, glutamate receptor trafficking, and synaptic stabilization (Pizzorusso et al, 2002;Frischknecht et al, 2009;Frischknecht and Gundelfinger, 2012;Carceller et al, 2020;Christensen et al, 2021). For example, removal of PNNs decreases densities of inhibitory and excitatory synapses on the soma of PVB neurons (Carceller et al, 2020), reduces gamma activity (Christensen et al, 2021), and de-stabilizes the grid cell network (Christensen et al, 2021). Several studies, including seminal work in the visual cortex and the amygdala, demonstrated that PNNs form during the end of critical periods The CSPG protease cathepsin-S is expressed in a diurnal manner by microglia in the mouse brain, antiphase to PNN composition rhythms.…”
Section: Extracellular Matrix: Evidence For Involvement In Memory Consolidationmentioning
confidence: 99%
“…They surround somata and proximal dendrites of certain types of neurons (Hockfield and McKay, 1983), being particularly enriched around parvalbumin-positive interneurons (PV+) (Kosaka and Heizmann, 1989;Fawcett et al, 2019). Perineuronal nets are well-recognized regulators of plasticity in the CNS which stabilize and consolidate the system (Banerjee et al, 2017;Christensen et al, 2021), and play an indispensable role in learning and memory (Wang and Fawcett, 2012;Sorg et al, 2016;Shen, 2018). Interference with perineuronal net formation by chondroitinase ABC (chABC) digestion of their sugar chains or genetic knockdown of PNN components has been shown to promote plasticity in multiple paradigms, including ocular dominance (Pizzorusso et al, 2002), drug-induced conditioned place preference (Xue et al, 2014;Slaker et al, 2015) and fear learning (Gogolla et al, 2009;Banerjee et al, 2017;Pignataro et al, 2017;Shi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%